Diseño de una estrategia comercial para el sistema de socios del Club Deportivo El Nacional. - Rosero Carpio, Rubén Darío (2014)
This research entitled " Design of a commercial system for strategic partners Club Deportivo El Nacional" is a contribution to both partners , supporters and leaders of this prestigious sporting club can change corporate image presented today the club based on better business and marketing strategy , thus contributing to the achievement of corporate goals and projecting to continuously improve . Firstly, a comprehensive analysis of the football industry is done to continue reviewing the current state of the club and what is the segment to which we focus, with a study on the preferences of potential customers in this case the partners. A description of the project based on the fundamental aspects that is focused currently CDN revenues to subsequently define the strategies that will be implemented is performed.An analysis of the environment which surrounds the club considering internal and external factors determining strengths , weaknesses, opportunities and threats with which the market will be focused defined .